2015
DOI: 10.1139/cjp-2014-0290
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray modulation in high and middle latitudes during solar cycles 22 and 23

Abstract: Galactic cosmic rays are modulated in the heliosphere primarily by the global merged interaction regions with intense magnetic fields, which leads to a decrease in galactic cosmic rays throughout the heliosphere. Using long-term averages of solar wind (SW) component parameters in addition to cosmic ray count rates of four neutron monitors with different rigidity cutoffs, we analyzed the effect of these SW components on the count rates under different interplanetary magnetic field (IMF) disturbance levels. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…They suggested that the modulation of galactic cosmic rays should have a significant component controlled by the state of the interplanetary magnetic fields as they are transported out from the sun and hence there should be a solar cycle effect on the drift of the cosmic rays in the heliosphere. This was corroborated recently by many other studies (Chillingarian and Mailyan, 2009;Okpala et al, 2015;Kudela and Sabbah, 2016). Recently, Thomas et al (2017) studied the diurnal variation of cosmic rays using decadal data.…”
Section: Solar Modulation Of Cosmic Rayssupporting
confidence: 60%
“…They suggested that the modulation of galactic cosmic rays should have a significant component controlled by the state of the interplanetary magnetic fields as they are transported out from the sun and hence there should be a solar cycle effect on the drift of the cosmic rays in the heliosphere. This was corroborated recently by many other studies (Chillingarian and Mailyan, 2009;Okpala et al, 2015;Kudela and Sabbah, 2016). Recently, Thomas et al (2017) studied the diurnal variation of cosmic rays using decadal data.…”
Section: Solar Modulation Of Cosmic Rayssupporting
confidence: 60%
“…In addition, the large difference during the rising phase of cycle 24 and near its peak is a reflection of the dependence of the flux on the geomagnetic disturbance which may also be related to the solar activity. Solar activity correlates well with geomagnetic activity since they are intricately connected (Okpala et al 2014), hence observation here is an indication of the indirect effect of solar activity on the CR flux especially on the observed association between Ap index and CR flux (see Table 3) [13].…”
Section: Heliospheric Modulation Of Gcr (During Quiet Days)supporting
confidence: 54%
“…Among such researchers include [3][4][5][6][7][8][9][10]. The simple harmonic analysis of the diurnal variation of CR has been applied by authors such as [11,12,9,6,10] and their linear association with different drivers investigated by a few works [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mishra and Mishra (2007) showed that sunspot numbers and coronal index showed better correlation with cosmic ray intensity during negative polarity than positive polarity of the solar magnetic cycle. Okpala et al (2015), analyzed the effect of some solar wind components on the count rates under different interplanetary magnetic field (IMF) disturbance levels and observed different roles for dynamic pressure and B z component of IMF.…”
Section: Introductionmentioning
confidence: 99%